Mengukur Warisan Pendidikan Aisyah RA: Studi Empiris tentang Kontribusinya terhadap Pedagogi Islam - Luthfiyah Mahrusah; Miftahur Rohman (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
Women's contributions to Islamic education have received insufficient attention and importance in Islamic history. Aisha RA, one of the wives of the Prophet Muhammad, played a central role in the development of Islamic education through hadith narration, moral education, and upholding equal educational rights. The background of this paper is to explore the contribution of Aisha RA in Islamic education and its relevance to the development of education today. The data for this research was collected through a literature study using primary sources such as books of hadith and secondary sources in the form of books and scientific articles. The takhrij hadith method was used to assess the validity of the traditions narrated by Aisha RA, while deductive and inductive analyses were applied to reach a comprehensive conclusion. Results have shown that Aisha RA was not only a hadith narrator with more than 2.210 hadiths but also greatly contributed to the formation of moral education values which originated in the family and to the reinforcement of the principle of equality of men and women in education. This research implies that an inclusive Islamic education, such as that conducted by Aisha RA, may be an important model for contemporary education systems based on equality and morality.